Plasma levels of circulating DNA are associated with outcome, but not with activation of coagulation in decompensated cirrhosis and ACLF - Annabel Blasi; Vishal C. Patel; Jelle Adelmeijer; Sarah Azarian; Fatima Aziz; Javier Fernández; William Bernal; Ton Lisman (JHEP Reports, 2019)
Background & Aims: Acute-on-chronic liver failure (ACLF) is a recently (re)defined syndrome of acute decompensation of cirrhosis that presents with extrahepatic organ failure(s) and poor outcome. Given the prominent role of inflammation and activation of coagulation in ACLF, we hypothesized that ACLF might be characterized by the generation of neutrophil extracellular traps (NETs), that could drive both activation of coagulation and progression of organ failure. Methods: We measured markers of circulating DNA, activation of coagulation, inflammation, and oxidative stress in 52 patients with acute decompensation (AD) of cirrhosis and 57 patients with ACLF on admission, and compared levels with 40 healthy controls. Results: All analytes were higher in patients compared to controls. Plasma levels of cell-free DNA, but not of the specific NET marker myeloperoxidase-DNA complexes were higher in patients with ACLF compared to AD cirrhosis. In addition, TAT complexes (coagulation), IL-6 (inflammation), and TBARS (oxidative stress) were higher in ACLF compared to AD. Markers for activation of coagulation were not associated with circulating DNA, IL-6, or TBARS. In contrast, levels of circulating DNA, IL-6, and TBARS were higher in patients with more severe disease, higher in patients with organ failure, and higher in patients that died within 30 days of admission. Importantly, myeloperoxidase-DNA levels did not differ between patients with complications and poor outcome. Conclusions: Collectively, we show that cell-free DNA, inflammation, and oxidative stress are associated with outcomes in AD and ACLF, but not with activation of coagulation. Our data argue against a role of NETs in activation of coagulation and in progression of organ failure in patients with AD and ACLF. Lay summary: Acute-on-chronic liver failure is a devastating syndrome that can follow acute decompensation of chronic liver disease. Herein, we demonstrate that these patients accumulate DNA released from dying cells in their blood, and that the quantity of this DNA is related to the outcome of disease. We also show that outcome of disease is not related to recently described neutrophil extracellular traps, which have been shown in animal models to play vital roles in the progression of liver diseases. Keywords: cirrhosis, liver, acute-on-chronic liver disease, neutrophil extracellular trap, coagulation, sepsis, mortality, inflammation, oxidative stress